2019
DOI: 10.1029/2018pa003488
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous Nannofossil Response to Climate Variability During the Middle Pleistocene Transition in the Northwest Pacific Ocean (Ocean Drilling Program Leg 198 Site 1209)

Abstract: The Middle Pleistocene Transition represents an important reorganization of climate that switched from a 41‐kyr periodicity to a quasiperiodic 100‐kyr cycle. Here, we have investigated this time interval using calcareous nannofossils from a midlatitude well‐preserved sedimentary record from the Ocean Drilling Program Site 1209 in the North West Pacific Ocean. We studied samples from 1.45 to 0.45 Ma, looking for significant changes in the nannofossil assemblages. Micropaleontological data were processed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
(192 reference statements)
0
2
0
Order By: Relevance
“…Radiolarian and planktonic foraminifer assemblages from North Pacific low latitudes (IODP Expedition 314–315; ODP Site 1144) indicated that warm and oligotrophic conditions persisted during most of the EMPT, between ~1.3 and 0.7 Ma (Wang et al, 2003 ; Zheng et al, 2005 ; Matsuzaki et al, 2015 ; Kubota et al, 2021 ), supporting the presence of a deep, stable thermocline. Similarly, calcareous nannofossil assemblages from Shatsky Rise (ODP Site 1209) suggest warm SSTs and stable conditions during the EMPT between ~ 1.2 and 0.62 Ma (Lupi et al, 2019 ). Interval 2: Middle–Late Pleistocene (post‐EMPT) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiolarian and planktonic foraminifer assemblages from North Pacific low latitudes (IODP Expedition 314–315; ODP Site 1144) indicated that warm and oligotrophic conditions persisted during most of the EMPT, between ~1.3 and 0.7 Ma (Wang et al, 2003 ; Zheng et al, 2005 ; Matsuzaki et al, 2015 ; Kubota et al, 2021 ), supporting the presence of a deep, stable thermocline. Similarly, calcareous nannofossil assemblages from Shatsky Rise (ODP Site 1209) suggest warm SSTs and stable conditions during the EMPT between ~ 1.2 and 0.62 Ma (Lupi et al, 2019 ). Interval 2: Middle–Late Pleistocene (post‐EMPT) …”
Section: Discussionmentioning
confidence: 99%
“…ENSO modelling indicates that this climate pattern could have been present in the past (Cane and Clement, 1999 ), and several studies recorded events probably attributable to ENSO variability in the Pleistocene (e.g. Pisias, 1978 ; Wang et al, 2000 ; Bordiga et al, 2014 ; Lupi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%